Contribution on Improving Power Resilience in the Healthcare Facility. - Rusdy Hartungi; L. J. Commis (International Journal of Smart Grid and Sustainable Energy Technologies, 2017)
Focused on predicting and preventing electrical failures, this paper presents methodologies to those responsible for managing the electrical supplies in Healthcare and other similar environments. Particular attention has been directed to developing ways of exploiting the known relationships between thermal and electrical engineering disciplines as a means of monitoring and informing a timely intervention. There are two major studies presented in this paper which contrubute resilience in specific areas of Healtcare Facility. The first study is focusing on thermography, it is enhanced with an application of the finite difference method for modelling thermal performance under adverse conditions has been analysed.Thsi methos could provide a more robust solution for appraising new and existing installations. Study shows that early identification. A second study was carried out to examine the use of weather forecast-based electrical site load predictions as a possible precursor to automated load shed control which found reliable correlation between a site’s peak electrical load and the peak outside air temperature. The use of weather forecast-based electrical site load will help reducing unnecessary tripping of the power supply and this increase resilience.